Donor impurity-related optical absorption in GaAs elliptic-shaped quantum dots (2017)
ABSTRACT: The conduction band and electron-donor impurity states in elliptic-shaped GaAs quantum dots under the effect of an externally applied electric field are calculated within the effective mass and adiabatic approximations using two different numerical approaches: a spectral scheme and the finite element method. The resulting energies and wave functions become the basic information needed to evaluate the interstate optical absorption in the system, which is reported as a function of the geometry, the electric field strength, and the temperature.